Integrin α11 in non–small cell lung cancer is associated with tumor progression and postoperative recurrence - Ando, Takahiro (Cancer Sci, 2019)
Integrins are transmembrane proteins that mediate cell adhesion to the extracellular matrix. Integrin α11 (ITGA11) is not expressed in normal alveolar epithelial cells and is a known receptor for collagen. While integrin α11β1 overexpression in the tumor stroma has been associated with tumor growth and metastatic potential of non–small cell lung cancer (NSCLC), little is known about the role of ITGA11 in tumor cells. Thus, we examined the RNA expression of ITGA11 by quantitative RT‐PCR in 80 samples collected from NSCLC patients who had undergone surgical resection and analyzed the clinical outcomes. We found that high expression of ITGA11 was associated with lower recurrence‐free survival in all NSCLC patients (P = 0.043) and in stage I NSCLC patients (P = 0.049). These results were consistent with in silico analyses of the Cancer Genome Atlas database. We also analyzed cell proliferation, migration and invasion capacity in lung cancer cell lines after overexpression of ITGA11. Overexpression of ITGA11 in lung cancer cell lines had little effect on cell proliferation but resulted in increased migration and invasion capacity. Our findings suggest that ITGA11 plays a significant role in cancer migration and invasion, leading to higher recurrence. ITGA11 expression may be a predictor of poor prognosis in patients with surgically resected NSCLC.